Management of Upper Airway Infantile Hemangiomas: Experience of One Italian Multidisciplinary Center - Corbeddu, Marialuisa; Meucci, Duino; Diociaiuti, Andrea; Giancristoforo, Simona; Rotunno, Roberta; Gonfiantini, Michaela Veronika; Trozzi, Marilena; Bottero, Sergio; El Hachem, May (Frontiers in Pediatrics, 2021)
Airway infantile hemangiomas (IHs) can represent a life-threatening condition since the first months of life. They may be isolated or associated to cutaneous IHs, and/or part of PHACES syndrome. Diagnosis, staging and indication to treatment are not standardized yet despite the presence in the literature of previous case series and reviews. The diagnosis might be misleading, especially in absence of cutaneous lesions. Airway endoscopy is the gold standard both for diagnosis and follow-up since it allows evaluation of precise localization and entity of obstruction and/or stricture. Proliferation of IH in the infant airways manifests frequently with stridor and treatment is required as soon as possible to prevent further complications. The first line therapy is oral propranolol, but duration of treatment is not yet well defined. All considered, we report the experience of our multidisciplinary center from 2009 to date, on 36 patients affected by airway IHs, and successfully treated with oral propranolol. Thus, the authors propose their experience for the management of airway IHs, specifically early diagnosis, when to perform endoscopy, how to interpret its findings, and when to stop the treatment.